Struggling to breathe: a qualitative study of children's wellbeing during lockdown in Spain. Issue 2 (1st February 2021) - Idoiaga Mondragon, Nahia; Berasategi Sancho, Naiara; Dosil Santamaria, Maria; Eiguren Munitis, Amaia
Abstract: Objective: COVID-19 has spread throughout the world, including Europe. In order to halt the spread of the pandemic by maintaining social distancing, all children in Spain have been completely confined to their homes, and from March 13th to April 26th they were forbidden from going outdoors at any time. The aim of this research was gather the voices of children in lockdown during the COVID-19 pandemic in Spain in order to examine how they are coping with this health crisis. Design: A sample of 250 Children from a region of Spain aged 3-12 years (mean 7.14) were openly asked about their lockdown activities, needs, and feelings. Main Outcome Measures: Responses were analyzed using Iramuteq software for lexical analysis. Results: Children reported having mixed emotions in lockdown; whilst they are happy and relaxed with their families, they also feel fear, nervousness, worry, loneliness, sadness, boredom, and anger. At a physical level, Children noted it was difficult to be deprived of fresh air for weeks, which also makes them primarily sedentary, and they missed outdoor exercise. Socially, they missed peers and caregivers. Conclusion: This study provides evidence about the need to safeguard children's wellbeing during the COVID-19 crisis.